2010
DOI: 10.1002/mabi.200900456
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Solvent Signal Offsets in the Analysis of Interferometric Sedimentation Velocity Data

Abstract: Sedimentation velocity (SV) analytical ultracentrifugation has re-emerged as an important tool in the characterization of biological macromolecules and nanoparticles. The computational analysis of the evolution of the macromolecular concentration profile allows the characterization of many hydrodynamic and thermodynamic properties of the macromolecules and their interactions. The Rayleigh interference optical system is often the detection method of choice, for its usually superior data quality and the wide app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…MBP used in this study contained the vector-derived sequence NAAAEFPAGN, which could promote non-specific dimerization. In support of this, when MBP was cloned and expressed without these additional amino acids, AUC revealed that the protein is monomeric at high concentrations (64). The species observed around s 20,w = 3.8 S (44 kDa) have estimated molecular masses in close agreement with the calculated molecular masses of the monomeric MBP-Vif(101–176) (50 kDa) and MBP-Vif(101–192) (52 kDa).…”
Section: Resultsmentioning
confidence: 85%
“…MBP used in this study contained the vector-derived sequence NAAAEFPAGN, which could promote non-specific dimerization. In support of this, when MBP was cloned and expressed without these additional amino acids, AUC revealed that the protein is monomeric at high concentrations (64). The species observed around s 20,w = 3.8 S (44 kDa) have estimated molecular masses in close agreement with the calculated molecular masses of the monomeric MBP-Vif(101–176) (50 kDa) and MBP-Vif(101–192) (52 kDa).…”
Section: Resultsmentioning
confidence: 85%
“…Experimentally, care has to be expressed in filling the cells – menisci in solvent and solution channels need to be carefully matched, otherwise necessitating extended models accounting for co-solvent re-distribution [45]. The scans to be included in the analysis should comprise representatively the entire sedimentation process, from the beginning of depletion near the meniscus from the sedimentation of the fastest species at early times up to the virtual complete sedimentation of the smallest species from the radial observation window.…”
Section: Discussionmentioning
confidence: 99%
“…100 scans were acquired at 7 minute intervals and a rotor speed of 50 krpm; absorbance data were collected as single absorbance measurements at 280 nm using a radial spacing of 0.003 cm. Data were analyzed in SEDFIT 12.1b [5] in terms of a continuous c( s ) distribution; when required the use of a buffer mismatch model was implemented in order to account for slight meniscus mismatches [65]. Solution densities ρ and viscosities η were calculated using the program SEDNTERP 1.09 [40].…”
Section: Methodsmentioning
confidence: 99%